Menumbuhkan Karakter Anak Usia Dini Melalui Cerita Boneka Tangan dalam Model Tadzkirah - Ridwan Ridwan; Widi Wulansari (International Consortium of Education and Culture Research Studies, 2019)
The growth of early childhood character in the golden age is a very important thing that affects behavior and character in the future and it is the responsibility of all parties. Various models, methods and media can be used as a means to grow characters in early childhood. One is using hand puppets through storytelling methods. This research is aimed to know how the use of hand puppet through story with tadzkirah model can grow character in early childhood. Kindergarten / PAUD students will be more interested in recognizing characters as well as emulating those characters in the story. Methods of telling stories with hand puppets in line with the tadzkirah learning model, emphasizing on exemplary (T), guidance on guidance (A), encouragement (D), planting value (Z), continuity principle (K) repetition (R), organizing knowledge and experience (A), touching heart (H). Methods in this study are qualitative methods. The conclusions of this study are the use of hand puppets through story methods and tadzkirah models containing stories of honesty, independence, sense of responsibility and tolerance can grow characters in early childhood.